Rapid self-reaction type water-soluble core material and preparation method thereof
By optimizing formula and wrapping technology, the dissolution rate of polyethylene glycol core materials in water is improved, and the problem of slow dissolution rate of polyethylene glycol core materials is solved, and efficient and accurate preparation of core materials is achieved. It is suitable for Complex inner cavity castings.
Patent Information
- Application Number
- CN202411431802.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-14
AI Technical Summary
The polyethylene glycol core material dissolves slowly in water, which affects the production efficiency of the wax mold cavity. Especially in the core material that is too long or too thin, the concentration gradient of the acid drops after deep dissolution, and the reaction speed slows down.
The fast self-reacting water-soluble core material with an optimized formulation, including the first polyethylene glycol, the second polyethylene glycol, an inert filler, an acid source and an alkali source, which is encapsulated in the first polyethylene glycol To avoid direct contact with acid, mix with other raw materials after forming fine powder, sprayer granulation to ensure that the reaction speed is accelerated when exposed to water.
It realizes rapid dissolution and dissolution of the core material without additional acid, improves production efficiency, small line shrinkage, high core dimensional accuracy, good surface finish, convenient use and safe environment.
Smart Images

Figure BDA0005083871840000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of casting, and in particular relates to a fast self-reactive water-soluble core material and a preparation method thereof. Background Art
[0002] In some precision castings such as automobiles and aircraft engines, there are often many complex holes and cavities of varying numbers and shapes that cannot be machined. Some cavities with particularly complex shapes, too long, or that do not allow for draft angles cannot be formed by mechanical core pulling. Water-soluble core technology can be used to form such cavities. Water-soluble core technology: first press the core material into a core mold, place the core mold into a model wax mold to press the wax mold, the core mold is wrapped in the model wax mold, and then the wax mold is completely immersed in dilute hydrochloric acid or dilute citric acid. The water-soluble core mold gradually dissolves from the wax mold to form the required wax mold cavity.
[0003] At present, the types of soluble core materials are mainly divided into salt core, gypsum core, ceramic core, urea core, polyethylene glycol core, etc. according to the core material. Urea core mold materials are easily decomposed by heat, have a strong odor, and the surface finish of the pressed model is not good. Generally, they are only used to produce ordinary precision casting cavities that do not require the quality of the casting cavity. At present, the most widely used is polyethylene glycol core material, which is mainly used in the inner cavity of precision castings that require high dimensional accuracy and surface quality of the casting cavity. However, polyethylene glycol core materials also have their own disadvantages: due to the high molecular weight (usually greater than 6000) model used in polyethylene glycol core materials, the dissolution rate is slow when immersed in water, and the core mold pressed with polyethylene glycol core material is coated in the model wax mold, and the surface area in contact with water is limited, which inhibits the dissolution rate of the core material to a certain extent and affects the production efficiency of the wax mold cavity. At present, the method to solve this technical problem is mainly to add other auxiliary materials, such as sodium bicarbonate as a co-solvent, to the polyethylene glycol core material, and at the same time immerse it in 5%-10% dilute hydrochloric acid or dilute citric acid to quickly dissolve. However, for a core material that is too long and too thin, as the outside dissolves deeply, the concentration gradient of the acid in contact with the core material will drop rapidly, and the reaction speed will become slower and slower.
[0004] Therefore, in view of the above technical problems, it is necessary to provide a fast self-reactive water-soluble core material and a preparation method thereof.
[0005] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention
[0006] The object of the present invention is to provide a fast self-reactive water-soluble core material and a preparation method thereof.
[0007] In order to achieve the above object, a technical solution provided by a specific embodiment of the present invention is as follows:
[0008] The raw material composition of the fast self-reactive water-soluble core material includes, by weight: a first polyethylene glycol, with a weight average molecular weight of 8000 to 20000: 0 to 10 parts; a second polyethylene glycol, with a weight average molecular weight of 1000 to 12000: 20 to 40 parts; an inert filler: 5 to 20 parts; an acid source: 5 to 25 parts; an alkali source: 5 to 30 parts; an anti-settling agent: 0 to 5 parts; and a desiccant: 0 to 1 part. Preferably, the weight average molecular weight of the first polyethylene glycol is 12000 to 20000. Preferably, the weight average molecular weight of the second polyethylene glycol is 4000 to 12000; and a further preferred molecular weight is 4000 to 10000.
[0009] In one or more embodiments of the present invention, the inert filler is selected from diatomaceous earth, talc, bentonite, kaolin, mica powder, and clay.
[0010] In one or more embodiments of the present invention, the particle size of the inert filler is 800 mesh to 1500 mesh.
[0011] In one or more embodiments of the present invention, the acid source is selected from organic acid and inorganic acid. The organic acid is selected from citric acid, fumaric acid, tartaric acid. The inorganic acid is selected from sulfuric acid, hydrochloric acid, phosphoric acid, and soluble hydrogen phosphate, dihydrogen phosphate, etc.
[0012] In one or more embodiments of the present invention, the alkali source is selected from calcium carbonate, potassium bicarbonate, potassium carbonate, sodium bicarbonate, sodium carbonate, sodium silicate, potassium silicate. Preferably, carbonate, bicarbonate, water-soluble silicate. More preferably, carbonate.
[0013] In one or more embodiments of the present invention, the alkali source is pre-coated with the first polyethylene glycol and granulated.
[0014] In one or more embodiments of the present invention, the alkali source is a first polyethylene glycol dissolved in anhydrous propyl alcohol to form a uniform mixed solution, which is then mixed with the alkali source and granulated by a sprayer. The polyethylene glycol wraps the sodium bicarbonate. This form of alkali source addition can effectively avoid direct contact with the acid before removal, thereby ensuring the storage stability of the product. Preferably, the alkali source is a first polyethylene glycol dissolved in anhydrous propyl alcohol to form a uniform mixed solution: the mass ratio of the first polyethylene glycol to the anhydrous propyl alcohol is 1: (2-5) at a temperature of 60°C-70°C, and stirred to form a uniform mixture.
[0015] In one or more embodiments of the present invention, the anti-settling agent is a polyamide wax powder anti-dust agent, which increases the viscosity of the system and makes the filler particles suspended in the system less likely to settle.
[0016] In one or more embodiments of the present invention, the desiccant is selected from CaO and CaCl2.
[0017] In one or more embodiments of the present invention, a method for preparing a fast self-reactive water-soluble core material comprises:
[0018] (1) heating and melting the first polyethylene glycol and anhydrous propylene glycol (melting temperature is 60° C.-70° C.), wherein the mass ratio of the first polyethylene glycol to the anhydrous propylene glycol is 1:(2-5), stirring to form a uniform liquid mixture, and then mixing with an alkali source, and forming a fine powder through a sprayer;
[0019] (2) After the second polyethylene glycol, inert filler, organic acid, and anti-settling agent are dispersed by stirring, the fine powder is added, and the stirring is continued to disperse uniformly to obtain a core material mixture.
[0020] Preferably, the method for preparing the fast self-reactive water-soluble core material of the present invention may include the following process steps:
[0021] (1) adding the first polyethylene glycol and anhydrous propanol in a ratio of 1:3 by weight into a container, heating and melting at 60° C. to 70° C., stirring to form a uniform liquid mixture, and then mixing with an alkali source, forming fine powder through a sprayer, and the high molecular weight polyethylene glycol wraps the alkali source;
[0022] (2) Add the second polyethylene glycol, inert filler, organic acid and anti-settling agent in the mixer at the above weight fraction. Control the temperature at 50°C-60°C, stir and disperse, then add the fine powder prepared above (polyethylene glycol coated alkali source), continue to stir and disperse evenly, and obtain a core material mixture.
[0023] During the application process, the mixture can be shaped in a mold, and the rapid self-reactive water-soluble core material can be obtained by cooling and demoulding.
[0024] Compared with the prior art, the fast self-reactive water-soluble core material and preparation method of the present invention achieves self-disintegration and dissolution after encountering water by optimizing the core formula without the need to add additional acid, thereby having better convenience of use and environmental safety. It can be reflected in the following aspects: (1) When the overly long and thin core mold coated in the model wax mold encounters water, the polyethylene glycol coating outside the alkali source dissolves in the water, the alkali source is released, and begins to react with the acid source. As the polyethylene glycol coating continues to dissolve, the alkali source concentration continues to increase, the reaction speed accelerates, and the core mold reaches rapid disintegration and dissolution; (2) The linear shrinkage rate is small, reaching less than 0.3%, and the core size accuracy is high; (3) The surface finish is good. DETAILED DESCRIPTION
[0025] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0026] Example 1
[0027] A fast self-reactive water-soluble core material comprises the following raw materials in parts by weight: 200004 parts of polyethylene glycol, 30 parts of polyethylene glycol 6000, 20 parts of 800-mesh diatomaceous earth, 20 parts of citric acid, 25 parts of sodium bicarbonate, 1 part of polyamide wax powder, and 0.5 parts of CaO.
[0028] The method for preparing the above-mentioned fast self-reactive water-soluble core material comprises the following steps:
[0029] (1) adding polyethylene glycol 20000 and anhydrous propanol in a ratio of 1:3 in a container, heating and melting at 60° C., stirring to form a uniform liquid mixture, and then mixing with sodium bicarbonate, forming fine powder through a sprayer, wherein the polyethylene glycol coats the sodium bicarbonate;
[0030] (2) Add polyethylene glycol 6000, diatomaceous earth, citric acid, 1 part of polyamide wax powder, and 0.5 part of CaO in the mixer at the above weight fractions, control the temperature to 50°C, stir and disperse, add the fine powder prepared above (sodium bicarbonate wrapped in polyethylene glycol), continue to stir and disperse evenly, obtain a core material mixture, shape it in a mold, cool and demold it, and then obtain the fast self-reactive water-soluble core material.
[0031] Example 2
[0032] A fast self-reactive water-soluble core material comprises the following raw materials in parts by weight: 160007 parts of polyethylene glycol, 400040 parts of polyethylene glycol, 800-mesh mica powder 10 parts, tartaric acid 20 parts, sodium carbonate 20 parts, polyamide wax powder 3 parts, and CaCl2 1 part.
[0033] The method for preparing the above-mentioned fast self-reactive water-soluble core material comprises the following steps:
[0034] (1) adding polyethylene glycol 16000 and anhydrous propanol in a ratio of 1:3 in a container, heating and melting at 60° C., stirring to form a uniform liquid mixture, and then mixing with sodium carbonate, forming fine powder through a sprayer, wherein the polyethylene glycol coats the sodium carbonate;
[0035] (2) Add polyethylene glycol 4000, tartaric acid, mica powder, polyamide wax powder and CaCl2 in the above weight fraction into a mixer, control the temperature to 50°C, stir and disperse, add the above-prepared fine powder (sodium carbonate wrapped in polyethylene glycol), continue to stir and disperse evenly to obtain a core material mixture, shape it in a mold, cool and demold it to obtain the fast self-reactive water-soluble core material.
[0036] Example 3
[0037] A fast self-reactive water-soluble core material comprises the following raw materials in parts by weight: 10 parts of polyethylene glycol 14000, 30 parts of polyethylene glycol 2000, 5 parts of 800-mesh bentonite, 25 parts of fumaric acid, 25 parts of potassium bicarbonate, 5 parts of polyamide wax powder, and 0.5 parts of CaCl2.
[0038] The method for preparing the above-mentioned fast self-reactive water-soluble core material comprises the following steps:
[0039] (1) adding polyethylene glycol 14000 and anhydrous propanol in a ratio of 1:3 in a container, heating and melting at 60° C., stirring to form a uniform liquid mixture, and then mixing with potassium bicarbonate to form fine powder through a sprayer, wherein the polyethylene glycol coats the potassium bicarbonate;
[0040] (2) Add polyethylene glycol 2000, potassium bicarbonate, fumaric acid, bentonite, polyamide wax powder and CaCl2 in the above weight fractions into a mixer, control the temperature to 50°C, stir and disperse, add the above-prepared fine powder (potassium bicarbonate wrapped in polyethylene glycol), continue to stir and disperse evenly to obtain a core material mixture, shape it in a mold, cool and demold it to obtain the fast self-reactive water-soluble core material.
[0041] Example 4
[0042] The difference between this embodiment and embodiment 2 is only that:
[0043] The fast self-reactive water-soluble core material comprises the following raw materials in parts by weight: 40 parts of polyethylene glycol 4000, 10 parts of 800-mesh mica powder, 20 parts of tartaric acid, 20 parts of sodium carbonate, 3 parts of polyamide wax powder, and 1 part of CaCl2.
[0044] Example 5
[0045] The difference between this embodiment and embodiment 2 is only that:
[0046] The fast self-reactive water-soluble core material comprises the following raw materials in parts by weight: 40 parts of polyethylene glycol 8000, 10 parts of 800-mesh mica powder, 20 parts of tartaric acid, 20 parts of sodium carbonate, 3 parts of polyamide wax powder, and 1 part of CaCl2.
[0047] Example 6
[0048] The difference between this embodiment and embodiment 2 is only that:
[0049] The fast self-reactive water-soluble core material comprises the following raw materials in parts by weight: 160007 parts of polyethylene glycol, 40 parts of polyethylene glycol 400040 parts, 10 parts of 1000 mesh mica powder, 20 parts of tartaric acid, 20 parts of sodium carbonate, 3 parts of polyamide wax powder and 1 part of CaCl2.
[0050] Example 7
[0051] The difference between this embodiment and embodiment 2 is only that:
[0052] The fast self-reactive water-soluble core material comprises the following raw materials in parts by weight: 160007 parts of polyethylene glycol, 40 parts of polyethylene glycol 400040 parts, 1500 mesh mica powder 10 parts, tartaric acid 20 parts, sodium carbonate 20 parts, polyamide wax powder 3 parts, and CaCl2 1 part.
[0053] Example 8
[0054] The difference between this embodiment and embodiment 2 is only that:
[0055] The fast self-reactive water-soluble core material comprises the following raw materials in parts by weight: 200007 parts of polyethylene glycol, 40 parts of polyethylene glycol, 10 parts of 800-mesh mica powder, 20 parts of tartaric acid, 20 parts of sodium carbonate, 3 parts of polyamide wax powder and 1 part of CaCl2.
[0056] Example 9
[0057] The difference between this embodiment and embodiment 2 is only that:
[0058] The fast self-reactive water-soluble core material comprises the following raw materials in parts by weight: 160007 parts of polyethylene glycol, 40 parts of polyethylene glycol 12000, 10 parts of 800-mesh mica powder, 20 parts of tartaric acid, 20 parts of sodium carbonate, 3 parts of polyamide wax powder, and 1 part of CaCl2.
[0059] Example 10
[0060] The difference between this embodiment and embodiment 2 is only that:
[0061] The fast self-reactive water-soluble core material comprises the following raw materials in parts by weight: 160007 parts of polyethylene glycol, 400020 parts of polyethylene glycol, 5 parts of 800-mesh mica powder, 5 parts of tartaric acid and 5 parts of sodium carbonate.
[0062] Embodiment 11
[0063] The difference between this embodiment and embodiment 2 is only that:
[0064] The preparation method comprises the following steps:
[0065] (1) adding the polyethylene glycol of the weight fraction and anhydrous propanol in a ratio of 1:2 into a container, heating and melting at 65° C., stirring to form a uniform liquid mixture, and then mixing with sodium carbonate, forming fine powder through a sprayer, wherein the polyethylene glycol coats the sodium carbonate;
[0066] (2) Add polyethylene glycol, tartaric acid, mica powder, polyamide wax powder and CaCl2 in the above weight fraction into a mixer, control the temperature to 55°C, stir and disperse, add the above-prepared fine powder (sodium carbonate wrapped in polyethylene glycol), continue to stir and disperse evenly to obtain a core material mixture, shape it in a mold, cool and demold it to obtain the fast self-reactive water-soluble core material.
[0067] Example 12
[0068] The difference between this embodiment and embodiment 2 is only that:
[0069] The preparation method comprises the following steps:
[0070] (1) adding the polyethylene glycol of the weight fraction and anhydrous propanol in a ratio of 1:5 into a container, heating and melting at 70° C., stirring to form a uniform liquid mixture, and then mixing with sodium carbonate, forming fine powder through a sprayer, wherein the polyethylene glycol coats the sodium carbonate;
[0071] (2) Add polyethylene glycol, tartaric acid, mica powder, polyamide wax powder and CaCl2 in the above weight fraction into a mixer, control the temperature to 60°C, stir and disperse, add the above-prepared fine powder (sodium carbonate wrapped in polyethylene glycol), continue to stir and disperse evenly to obtain a core material mixture, shape it in a mold, cool and demold it to obtain the fast self-reactive water-soluble core material.
[0072] Comparative Example 1
[0073] The only difference between this comparative example and Example 1 is that no citric acid is added.
[0074] Comparative Example 2
[0075] The difference between this comparative example and Example 2 is only that tartaric acid is not added.
[0076] Water solubility rate test method: first press a test piece of 40mm×20mm×6mm, put it into water at room temperature 25℃, and measure the time it takes for the test piece to be completely dissolved.
[0077] The linear shrinkage is tested according to GB / T 14235.1.
[0078] The performance test results of the embodiments and comparative examples of the present invention are shown in the following table:
[0079]
[0080] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0081] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A fast self-reactive water-soluble core material, the raw material composition of which includes, in parts by weight: a first polyethylene glycol, with a weight average molecular weight of 8000 to 20000: 0 parts to 10 parts; The second polyethylene glycol, weight average molecular weight 1000-12000: 20-40 parts; inert filler: 5-20 parts; Acid source: 5 parts to 25 parts; Alkali source: 5 parts to 30 parts; Anti-settling agent: 0 parts to 5 parts; Desiccant: 0 to 1 part.
2. The fast self-reactive water-soluble core material according to claim 1, characterized in that: The inert filler is selected from diatomaceous earth, talc, bentonite, kaolin, mica powder and white clay.
3. The fast self-reactive water-soluble core material according to claim 2, characterized in that: The particle size of the inert filler is 800-1500 mesh.
4. The fast self-reactive water-soluble core material according to claim 1, characterized in that: The acid source is selected from organic acid and inorganic acid.
5. The fast self-reactive water-soluble core material according to claim 1, characterized in that: The alkali source is selected from calcium carbonate, potassium bicarbonate, potassium carbonate, sodium bicarbonate, sodium carbonate, sodium silicate, and potassium silicate.
6. The fast self-reactive water-soluble core material according to claim 5, characterized in that: The alkaline source is pre-coated with the first polyethylene glycol and granulated.
7. The fast self-reactive water-soluble core material according to claim 6, characterized in that: The alkali source is a first polyethylene glycol dissolved in anhydrous propanol to form a uniform mixed solution, which is then mixed with the alkali source and granulated by a sprayer.
8. The fast self-reactive water-soluble core material according to claim 1, characterized in that: The anti-settling agent is a polyamide wax powder anti-dust agent.
9. The fast self-reactive water-soluble core material according to claim 1, characterized in that: The desiccant is selected from CaO and CaCl2.
10. A method for preparing a fast self-reactive water-soluble core material according to any one of claims 1 to 9, comprising: (1) heating and melting the first polyethylene glycol and anhydrous propyl alcohol, stirring to form a uniform liquid mixture, and then mixing with an alkali source to form a fine powder through a sprayer; (2) After the second polyethylene glycol, inert filler, organic acid, and anti-settling agent are dispersed by stirring, the fine powder is added, and the stirring is continued to disperse uniformly to obtain a core material mixture.